A survey for low-luminosity quasars at redshift z similar to 5 - Sharp, R; Crampton, D; Hook, I; McMahon, R (2004)
We present the results of a multicolour (VIZ) survey for low-luminosity (M B < -23.5) quasars with z ∼ 5 using the 12K CCD mosaic camera on the Canada-France-Hawaii Telescope (CFHT). The survey covers 1.8 deg 2 to a limiting magnitude of m z = 22.5(Vega), about two magnitudes fainter than the SDSS (Sloan Digital Sky Survey) quasar survey. Twenty candidates were selected by their VIZ colours, and spectra for 15 of these were obtained with GMOS on the Gemini North telescope. A single quasar with z = 4.99 was recovered; the remaining candidates are all M stars. The detection of only a single quasar in the redshift range 4.8 < z < 5.2 accessible to the survey is indicative of a possible turnover in the luminosity function at faint quasar magnitudes, and a departure from the form observed at higher luminosities (in agreement with quasar lensing observations by Richards et al.). However, the derived space densities of quasars more luminous than MB (Vega) < - 23.5, of 2.96 × 10 -7 Mpc -3 is consistent at the 65 per cent confidence level with extrapolation of the quasar luminosity function as derived by Fan et al. at m i < 19.6(Vega).